On Future War : The Most Radical Reinterpretation of Armed Conflict since Clausewitz - Van Creveld, Martin (Rawalpindi Army Education Press, 1996)
An examination of the nature of war and its radical transformation in our own time. The author argues that the Clausewitzian assumption that war is rational is outdated, and that strategic, logical planning is unrelated to the current realities of guerrilla armies, terrorists and bandits.
Include Bibliography and Index.
Keywords: War -- Military art and science -- Military history, Modern -- World politics